2016
DOI: 10.1002/jcb.25808
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: MiR‐892a Promotes Hepatocellular Carcinoma Cells Proliferation and Invasion Through Targeting CD226

Abstract: Our study is aim to investigate the influence of miR-892a on proliferative and invasive activities of human hepatocellular carcinoma (HCC) cells through regulating CD226 expression. QRT-PCR was used to detect the expression levels of miR-892a and CD226 mRNA in HCC tissues and adjacent tissues or HCC cells and normal cells whereas Western Blot was used to detect the CD226 protein expression in tissue and cell samples. Then HuH-7 cell line was selected for following assays and respectively transfected with miR-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In recent years, some researches began to pay attention to the expression of CD226 in tumor cells. These studies found that expression of CD226 on hepatoma cells was down-regulated and that expression was related to the survival rate and survival time of patients (Baoxing et al, 2017). In addition, CD226 gene polymorphism was found to be directly related to tumor risk (Shaoqing et al, 2013).…”
Section: Cd226 and Tumorsmentioning
confidence: 97%
“…In recent years, some researches began to pay attention to the expression of CD226 in tumor cells. These studies found that expression of CD226 on hepatoma cells was down-regulated and that expression was related to the survival rate and survival time of patients (Baoxing et al, 2017). In addition, CD226 gene polymorphism was found to be directly related to tumor risk (Shaoqing et al, 2013).…”
Section: Cd226 and Tumorsmentioning
confidence: 97%
“…Our laboratory has also been committed to the study of cancer biomarkers for patient prognosis. [18][19][20][21] In this study, we found that HK1 participates in the glycolysis of OC cells and may be an independent biomarker for the poor prognosis of OC patients. Glucose metabolism enzymes are associated with cancer prognosis.…”
Section: Discussionmentioning
confidence: 55%
“…While in HCC-favorable gene set, many genes have been identified to be associated with HCC, such as VIPR1, CPEB3, HTR2A-AS1, ACSM3, ADRA1A, AKR1D1, BHMT, CD226, CD5L, CYP3A4, CYP3A43, DMGDH, ESR1, GLYATL1 and RDH16. Low expression of VIPR1 had an adverse prognostic impact on HCC [20], loss of ACSM3 expression was found to correlate with advanced HCC stages and a poor survival [21], down-regulation of BHMT in HCC associates with poor prognosis [22], low-expressed of CD226 could promote proliferative, migrating, and invasive activities of HCC cells [23], down-regulation of CYP3A4 gene is an independent predictor of early recurrence of HCC [24]. The results of the previous study were consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%